Comparative analysis of the national biosafety regulatory systems in East Africa - Jaffe, Gregory (International Food Policy Research Institute, 2006)
This paper analyzes the current and proposed biosafety systems in Kenya, Tanzania, and Uganda using a set of components and characteristics common to functional and protective biosafety regulatory systems. It also assesses how those systems take into account the major international legal obligations that relate to biosafety, such the Cartagena Biosafety Protocol. The paper identifies certain areas in each country’s biosafety regulatory systems where further development and clarification would improve the biosafety system, making it more functional and protective. Those areas include: (1) the addition of procedures to ensure the food safety of genetically engineered organisms; (2) the inclusion of the standard and criteria for making an approval decision; (3) the differentiation of regulatory procedures based on the relative risk of the organism; and (4) an explanation of how socio-economic considerations will be defined and assessed. Finally, the paper discusses possible ways the three countries can coordinate and harmonize their national biosafety regulatory systems so they are efficient, effective and make the best use of limited scientific and legal capacity.